2013
DOI: 10.1590/s0100-69162013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Volume of polyethylene bags for development of papaya seedlings in protected environments

Abstract: The objective of this study was to test container of polyethylene bags and protected environments on the papaya seedlings production, from May to August of 2008, in Aquidauana state of Mato Grosso do Sul (MS), Brazil. Five bags of polyethylene were used: 7.5 cm x 11.5 cm, 205.9 cm³; 8.4 cm x 10.6 cm, 238.1cm³; 10.0 cm x 16.5 cm, 525.2 cm³; 12.0 cm x 12.0 cm, 550.0 cm³ and 15.0 cm x 21.5 cm, 1539.8 cm³. These containers were placed in three protected environments: greenhouse; screened nursery with Sombrite® and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…According to OLIVEIRA et al (2012), plant ambience aims to identify the best weather conditions on production area and get better seedlings, yields and productivities. FARIA et al (2013) reported that the use of structures to protect the seedlings is very important when they are well managed, providing high quality plants with better adaptation to the field. COSTA et al (2010) explain that the different greenhouse environments use mostly the shading screens and plastic film.…”
Section: Introductionmentioning
confidence: 99%
“…According to OLIVEIRA et al (2012), plant ambience aims to identify the best weather conditions on production area and get better seedlings, yields and productivities. FARIA et al (2013) reported that the use of structures to protect the seedlings is very important when they are well managed, providing high quality plants with better adaptation to the field. COSTA et al (2010) explain that the different greenhouse environments use mostly the shading screens and plastic film.…”
Section: Introductionmentioning
confidence: 99%
“…Antoniazzi et al (2013), ao trabalhar com mudas de cedro (Cedrela fissilis Vell.) constataram que mudas Faria et al (2013), testando o volume de sacos de polietileno no desenvolvimento de mudas de mamoeiro em ambientes protegidos verificou que as mudas produzidas em sacos de menor volume sofreu com restrição ao desenvolvimento radicular e consequentemente, houve menor taxa do crescimento de impulso, assim como a disponibilidade de nutrientes nesses recipientes, resultado semelhante aos encontrados por Carvalho Filho et al 2003 2013, afirmam que mudas de espécies florestais e frutíferas obtêm melhores médias para as características avaliadas em recipientes de maiores volumes, portanto, quanto maior o volume do recipiente, menor é o número de replante, podendo ser associado então ao maior volume de raízes, diminuindo prováveis efeitos de seca que podem atingir o experimento.…”
Section: Resultsunclassified
“…En períodos de mayor precipitación, el invernadero, en comparación con las pantallas, permite plantas más grandes con mayor número de hojas (Costa et al, 2011). En un período de temperatura media, tanto el invernadero agrícola como la pantalla negra promueven plántulas de calidad para el grupo 'Sunrise Solo' (Faria et al, 2013). La pantalla de sombreado bajo la película de polietileno promueve una mayor velocidad de emergencia de plántulas de papaya del grupo 'Formosa' (Silva et al, 2013) y la pantalla de sombreado de 18 y 35% origina plántulas con mayor altura de planta, diámetro de tallo, materia seca y el índice de calidad de Dickson que la pantalla de sombreado de 0 y 50% (Salles et al, 2019).…”
Section: Introductionunclassified